2022
DOI: 10.3390/biomimetics8010010
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Drug Delivery of Hexagonal Boron Nitride-Borate Bioactive Glass Biomimetic Scaffolds for Bone Tissue Engineering

Abstract: In this study, biomimetic borate-based bioactive glass scaffolds containing hexagonal boron nitride hBN nanoparticles (0.1, 0.2, 0.5, 1, and 2% by weight) were manufactured with the polymer foam replication technique to be used in hard tissue engineering and drug delivery applications. To create three-dimensional cylindrical-shaped scaffolds, polyurethane foams were used as templates and covered using a suspension of glass and hBN powder mixture. Then, a heat treatment was applied at 570 °C in an air atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Previous studies also indicated that bioactive glass scaffolds induced IGF, VEGF, and PDGF in bone tissue for fracture site healing [32]. Until now, studies about bioactive glass scaffolds suggested enhancing the structure with different agents, metals [29,[33][34][35], mesenchymal stem cell coated [36], bone morphogenetic protein2 (BMP2) embedded [37], and PLA, poly-glycolic acid (PGA), polycaprolactone (PCL)-based biomaterials [38,39]. Further, in vivo studies are required to improve the effectiveness of bioactive glass scaffolds in the corporation of therapeutic agents in bone fracture healing.…”
Section: Bioactive Glass Scaffoldsmentioning
confidence: 99%
“…Previous studies also indicated that bioactive glass scaffolds induced IGF, VEGF, and PDGF in bone tissue for fracture site healing [32]. Until now, studies about bioactive glass scaffolds suggested enhancing the structure with different agents, metals [29,[33][34][35], mesenchymal stem cell coated [36], bone morphogenetic protein2 (BMP2) embedded [37], and PLA, poly-glycolic acid (PGA), polycaprolactone (PCL)-based biomaterials [38,39]. Further, in vivo studies are required to improve the effectiveness of bioactive glass scaffolds in the corporation of therapeutic agents in bone fracture healing.…”
Section: Bioactive Glass Scaffoldsmentioning
confidence: 99%
“…Finally, the biocompatibility and the adhesive properties of TPU vs. NIH-3T3 fibroblasts were assessed [49,50] and are shown in Figure 8 and summarized in Table 1. Panel A reports data obtained from the indirect cytotoxicity assay, where the content of TPU, released overnight in the cell medium, was tested on cells.…”
Section: Evaluation Of Tpu Surface Effect On Platelets Fibrinogen And...mentioning
confidence: 99%